Design and Manufacture of a Custom Ligament Loading Device for Use with Second Harmonic Generation Microscopy - Sevick, Johnathan; Xu, Minjia; Courat, Marine; Andrews, Stephen; Shrive, Nigel (CMBES Proceedings, 2016)
Ligament insertions into bone (entheses) represent a natural adaptation to severe material mismatch. Load is transferred from relatively flexible connective tissue to relatively inflexible bone over typically not more than a millimeter. Adequate load transfer at an insertion site is necessary for normal joint function while preventing injury. A few models have been used to assess different aspects of insertional mechanics, but all suffer from limitations. Most importantly, there has been an inability to observe the behaviour of entheses under applied load. An accurate description of enthesis load transfer mechanics has thus been lacking. A relatively new and powerful microscopic technology, second-harmonic generation (SHG), for which the University of Calgary has recently acquired an advanced microscope, has been shown to image movement on a microscale and is a promising tool to overcome the first of these difficulties, microscopic observation. The remaining difficulty remains the precise loading of ligaments during SHG imaging, highlighting the need for a custom-built loading device. Ligament loading is not an unfamiliar procedure and commercially available equipment exists to do so, however, the infrastructure for simultaneously loading and microscopically imaging entheses does not exist. The purpose of this work is to detail the device design process, from concept to manufacture, emphasizing the solutions to the design’s unique constraints and objectives and how they were determined. This includes the consolidation of a number of custom-machined components and commercially available hardware (for example: linear rail guides, strain gauges and precision motors).